JUST MEDICINE ANDROID APPLICATION A REVIEW - SHRUTI TIWARI,; SHALAKA MISHRA,; MRUNALI PARATE,; SHWETA JAMINKAR , (International Journal of Innovations in Engineering Research and Technology, 2021)
Just medicine application is project by the company Cluebix software pvt. Ltd[1].It will help users to search medicines via location by just one click or swipe of screen. This application ensures quality life which will improve healthcare system. It provides more faster and reliable online access to location of medical stores, medicines with great variety of recommended as well as non prescribed medicines and other healthcare products, easily accessible all over India. Even rural and urban areas can now have access to recent medications. It provides medical store name, its address and contact information. It continues a legacy of 200 years of success in the medical and chemical sciences. It involves secure, effective and reasonable medicinal stores as well as a customer wisdom that is value of user’s fidelity. It offers effortless navigation, more modern applications based on health care system, including clinical applications, medicines review for efficacy and safety, and access to information of drug.